Pharmacotheraphy in fibromyalgia syndrome - Özgöçmen, S.; Ardiço?lu, Ö. (My University, 2000)
Fibromyalgia syndrome is a chronic pain syndrome characterised by widespread pain and tenderness of musculokeletal structures. Alternatives in pharmacological treatment of this syndrome are so limited. In this paper drugs used in the treatment of fibromyalgia syndrome are reviewed.
Fibromiyalji sendromunda farmakoterapi
Keywords: alprazolam; amitriptyline; benzodiazepine derivative; clomipramine; cyclobenzaprine; dosulepin; maprotiline; serotonin; serotonin uptake inhibitor; tricyclic antidepressant agent; chronic pain; clinical trial; depression; drug indication; fibromyalgia; human; musculoskeletal system; review